2001
DOI: 10.1046/j.1440-1827.2001.01243.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of bone morphogenetic proteins in colon carcinoma with heterotopic ossification

Abstract: Here we report the case of a 50-year-old woman with adenocarcinoma of the colon, showing heterotopic ossification. The patient was referred to our hospital for investigation of anemia secondary to occult gastrointestinal blood loss. By colonoscopy, an irregular polypoid mass was found in the ascending colon. A biopsy of the lesion revealed moderately to poorly differentiated adenocarcinoma with heterotopic ossification. A right hemicolectomy was done and revealed areas of heterotopic bone within the tumor, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 48 publications
1
66
2
Order By: Relevance
“…4,18,25 Differentiation of these mesenchymal cells into osteoblasts causes production of BMPs, factors necessary for bone formation. In a previous analysis reported by Imai et al, 9 BMP-5 and BMP-6 were present in all tumor cells from an ossified colon cancer, with BMP-2 and BMP-4 present in only the cells surrounding the sites of ossification. It is thought that BMP-5 and BMP-6 expression induces differentiation of surrounding mesenchymal cells into preosteoblasts that express BMP-2 and BMP-4.…”
Section: 6mentioning
confidence: 69%
See 2 more Smart Citations
“…4,18,25 Differentiation of these mesenchymal cells into osteoblasts causes production of BMPs, factors necessary for bone formation. In a previous analysis reported by Imai et al, 9 BMP-5 and BMP-6 were present in all tumor cells from an ossified colon cancer, with BMP-2 and BMP-4 present in only the cells surrounding the sites of ossification. It is thought that BMP-5 and BMP-6 expression induces differentiation of surrounding mesenchymal cells into preosteoblasts that express BMP-2 and BMP-4.…”
Section: 6mentioning
confidence: 69%
“…It is thought that BMP-5 and BMP-6 expression induces differentiation of surrounding mesenchymal cells into preosteoblasts that express BMP-2 and BMP-4. 9 In ossified rectal and lung cancers, BMP-2 has been found to be expressed in many tumor cells. 16,31 Additional factors are needed for bone maturation, namely Runx2 and osterix; VEGF also assists in the differentiation and migration of hematopoietic cells into the spaces between trabeculae to form marrow.…”
Section: 6mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that bone morphogenetic protein 2 (BMP2), known to be a primary inducer of bone formation, plays an important role in heterotopic ossification in several types of cancer. [1][2][3] Interestingly, a more recent study found that coordination of BMP2 and Wnt/β-catenin signaling may be involved in the process of osteoplastic differentiation and subsequent bone formation, 4 while β-catenin has also been reported to induce BMP2 expression in gastrointestinal cancer cells. 5 We report a case of adrenal ML showing heterotopic bone formation with overexpression of BMP2 and β-catenin, indicating the possible involvement of BMP2 and the Wnt/β-catenin signaling pathway in heterotopic ossification.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, BMP6 has been report that it may play an important role in heterotopic ossification in colon adenocarcinoma. It is prominent in the cytoplasm of tumor cells, and it stains weakly in osteoblast-like cells adjacent to newly formed bone [11]. On the other hand, several reports suggested that BMP6 promoter methylation status is correlated with cancer.…”
Section: Introduction Background and Rationalementioning
confidence: 99%